The illusion of “The Garden”. A reflection on the works and ideas of the painter Hieronymus Bosch, through the perspective of present day thinkers and concepts - Tudor Jucan (Anastasis: Research in Medieval Culture and Art, 2021)
We are Introduced of the subject matter of the article, the description of the chosen work by H Bosch, the triptych entitled: “The Garden of Earthly Delights” there is also a detailedphysical description of the work itself and of the concepts and ideas the Dutch painter plays with. We oversee the ambiguity of the interpretation normally given to the central panel mostly but create a dialogue with the narratives of the other two, thus the conceptual intention of the author is presented (the work itself by being in some’s opinion a testimony to the uprising of the enlightenment (humanist) movements and the beginning of the Renaissance Era that took Europe and the World by storm… Although his images and ideas still echo in our present, by this reason we will employ the opinions of selected freethinkers that, in e strange way, engage the todays audience with the same concepts but somehow in a different paradigm: Paradise, Heaven, Heavenly Ecstasy, fear, acceptance etc. are just some of the forth mentioned subjects.The opinions will be set side by side to reveal the similarities or differences of Bosch’s symbolism within present day concepts. The Illusion behind the concept of Heaven… or better said of the promised Garden; But also the necessity of heaving a wishful ideal to live up to… the concept of purposefulness, mindfulness switches the role of Paradise, and how to obtain it with, the lifetime goal for a happier life and a place within a peaceful inner self. In conclusion we can observe, the visionary aspect of the work itself and how the viewer can receivea new perspective on old subjects. By creating this conceptual bridge, we are all the closer to understanding how we are more similar with our forefathers, and how even from a 500-year-old painting we can still learn a thing or two about the present.